Propofol attenuates angiogenesis by activating endoplasmic reticulum stress to suppress TFAP2C-driven VEGFA transcription - Fan Yang; Yi Liu; Hui Li; Xue Shang; Qing Hua; Yun Zhu; Beibei Tao; Zhirong Sun (Apoptosis, 2026)
During anesthesia, significant hemodynamic changes often alter the vascular microenvironment and affecting endothelial cell behavior. Propofol, a commonly used intravenous anesthetic, has been widely studied for its role in tumor angiogenesis through tumor cell–derived VEGF–mediated endothelial interactions. However, its direct effects on endothelial cell–mediated angiogenesis in non-malignant diseases such as diabetic retinopathy, diabetic nephropathy, and coronary heart disease remain unclear. To address this gap, we examined the effects of propofol on VEGFA-mediated angiogenesis in vitro and in vivo. Mechanistically, propofol triggers endoplasmic reticulum stress by promoting phosphorylation of PERK and its downstream effector eIF2α, leading to suppressed translation of TFAP2C—a transcription factor critical for endothelial function. Further analysis revealed that TFAP2C directly binds to the VEGFA promoter to activate its transcription, thereby facilitating VEGFA/VEGFR2-dependent angiogenesis. Together, these findings not only broaden the understanding of propofol’s pharmacological profile, but also identify TFAP2C as a novel transcriptional regulator of VEGFA, offering new perspectives for therapeutic targeting of VEGFA-mediated angiogenesis. Graphical abstract Schematic representation of the mechanism of propofol inhibition of VEGFA/VEGFR2-associated angiogenesis via the PERK/eIF2α/TFAP2C axis.